1992
DOI: 10.1103/physrevb.45.249
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen stoichiometry on the antiferromagnetic ordering of single crystals ofLa2NiO4+

Abstract: We report here on magnetic measurements of well-characterized single crystals of La&Ni04+q, for H both parallel and perpendicular to the c axis, and for compositions in the range 0 (5&0.067. The antiferromagnetic ordering temperature is shown to be very sensitive to the oxygen stoichiometry parameter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…[1]. This ferromagnetic behavior is very similar to previous observations on nearly stoichiometric La NiO obtained by annealing the oxidized precursor under reducing conditions (14,15). In these samples, the ferromagnetic contribution could be suspected to originate from Ni species.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…[1]. This ferromagnetic behavior is very similar to previous observations on nearly stoichiometric La NiO obtained by annealing the oxidized precursor under reducing conditions (14,15). In these samples, the ferromagnetic contribution could be suspected to originate from Ni species.…”
Section: Resultssupporting
confidence: 84%
“…We suspect the accident seen here and the one reported by Tranquada et al to have a similar origin. In many cases, low-temperature magnetizations have shown thermoremanent phenomena (5,14,15). We have effectively observed a systematic difference between fieldcooled (FC) and zero-field-cooled (ZFC) procedures when measuring magnetization below 50 K. Moreover, in the compound La NiO (ceramic sample) we have followed the magnetization decay versus time at 4 K after a FC procedure (16).…”
Section: Resultsmentioning
confidence: 96%
“…Earlier studies indicated T N around 650 K [30,42,43], but later [25] this was shown to be caused by the presence of metallic Ni, which has a Curie point at 633 K. The value of the magnetic moment per Ni-atom is assessed as 1.58 ± 0.1µ B based on neutron diffraction measurements [18,25,30]. Both the La 3 Ni 2 O 7 and La 4 Ni 3 O 10 phases crystallize in the orthorhombic cell (Table 1).…”
Section: Solid Phasesmentioning
confidence: 99%
“…Concerning the magnetic order, it has been shown that La 2 NiO 4 is an antiferromagnet with an in-plane ordering such that an antiferromagnetic (AF) interaction between nearest-neighbor Ni atoms is stabilized. The commensurability of the ordering has been put into question, 27 but careful studies with respect to the oxygen content show how the Néel temperature is significant even at values of δ ∼ 0.1, 28 and could vanish at δ ∼ 0.14. 19 We will focus our calculations in that doping level (δ 0.15), close to the localized electron limit where magnetic order is present at low temperature and our DFT calculations, which assume a magnetically ordered phase at zero temperature, can describe the system more accurately.…”
Section: Introductionmentioning
confidence: 99%